Performance evaluation of dye sensitized solar cell for variation TiO2 thicknesses - Muhammad Fitra, Zambak
Dye sensitized nanotitanium dioxide (TiO2) solar cell (DSSC) is a type of solar cell that utilises the usage of dye as to absorp more sun rays on solar cells and to direct solar irradiance in it as to circulate electron. The components used to build a nanotitanium dioxide (TiO2) dye sensitized solar cells can be divided into 4 parts in this case the nanotitanium dioxide (TiO2) as the anode and carbon as the counter electrode, soaking it in dye which act as absorption mechanism, adding of electrolyte and finally assembling them as a unit of solar cell. The process of solar absorption works as the photons from the sun molecular works similarly as in photosynthesis of green leaves. A Dye sensitized nanotitanium dioxide (TiO2) solar cell with a dimension of 6 x 2 cm is fabricated with variation thickness of 40 μm, 80 μm and 120 μm of nanotitanium dioxide (TiO2) by smearing it on an indium tin oxide (ITO) coated glass. It is then tested under the average solar irradiance and temperature of 693.69 W/m2, 44.4 oC respectively. This thesis proposes the use of syzigium oleina fruit as a novel organic dye. Syzigium oleina is a genus of flowering plants that belongs to the myrtle family, myrtaceae. The usage of syzigium oleina as dye compared to blueberries shows higher solar irradiance absorption and can be used as alternative of other types of organic berries. This thesis also proposes an alternative source of carbon material from recycled battery for the fabrication of the counter electrode of a dye sensitized solar cell. Based on experimental investigation for different thickness of 40 μm, 80 μm and 120 μm, result shows that the open circuit voltage, Voc value is 0.21 V, 0.16 V and 0.00063 V, respectively while the short circuit Jsc are 121.28 μA, 69.89 μA and 0 μA, respectively while the cells efficiency (η) are 4.92%, 2.66% and 0% and fill factor (FF) values are 1.1845, 1.49 and 0 respectively. Results indicates that the thinner the TiO2 coating thickness the better the solar cells performance and by using syzigium oleina as a novel dye it does increases the solar cells efficiency. Result also shows that by using carbon from recycle battery it helps in increasing the solar efficiency to 9.78 %. Based on prices, cost of fabricated 100 Watt DSSC is RM 688.05, with materials TiO2, Indium tin oxide coated glass, TritonX-100, Methoxyproprionitrile, syzigium oleina as dye, carbon from recycle battery. We have chosen these materials because their combination has resulted in the best DSSC device so far, cheap and green energy and save RM 204,435.00 if compare than market price type of PV module is 100 W monocrystalline with price of RM 750.00 per module.